Towards a Universal Digital Identity: a blockchain-based framework for borderless verification - Akhison, Glad (Frontiers in Blockchain, 2025)
IntroductionIdentity is the cornerstone of trust in modern society, yet current systems remain fragmented, document-based, and restricted by national boundaries. Physical passports, national identity cards, and paper records continue to define global mobility and access to services, despite being vulnerable to fraud, inefficiency, and exclusion. In today’s hyperconnected world, human mobility and digital finance have outgrown the boundaries of national identity systems. A traveller can fly from Kigali to London, study in Dubai, and work remotely for a company in Singapore, yet must repeatedly prove who they are through different passports, bank documents, and local IDs. This fragmentation slows innovation, increases compliance costs, and excludes millions who live or work across borders.MethodsThis paper argues for the establishment of a universal digital identity (UDI) hosted on a decentralised blockchain network. Under this model, each individual undergoes a one-time biometric enrolment capturing face, fingerprint, and voice data secured through cryptographic hashing and immutably stored on a blockchain ledger. A unique digital identity number (UDIN) is then generated, enabling retrieval of identity records worldwide by authorised institutions. Verification may occur in two ways: by presenting the UDIN or by frictionless biometric authentication, such as smiling at a camera or placing a finger on a scanner, instantly confirming identity against the blockchain.ResultsThis system eliminates the need for physical documents, reduces fraud, lowers compliance costs, and enhances global mobility and inclusion. With one ID recognised globally, a person can open a bank account in any country, cross borders securely, and interact in the global economy without friction, paperwork, or repeated verification.DiscussionThe paper sets out the vision, necessity, operational framework, and implications of a blockchain-based UDI, arguing that such a transformation is both inevitable and essential for the future of the digital economy. The Universal Digital Identity (UDI) envisions a world where a single, verifiable digital credential enables seamless travel, banking, and access to services anywhere on the planet.